Effect of COVID-19 on mortality due to diabetes mellitus in Brazil: A time series analysis from 2010 to 2023 - Larissa Otaviano Mesquita; Debora França dos Santos; Kenia Mara Baiocchi de Carvalho (PLoS ONE, 2026)
Diabetes mellitus (DM) is a major global public health concern, particularly in Brazil. This study aimed to analyze DM-related mortality trends before and during the pandemic to assess the possible influence of the COVID-19 pandemic on DM mortality in Brazil. Mortality was assessed using standardized mortality rates stratified by age group (20–29 years, 30–49 years, 50–69 years, 70 years or older), sex (male, female), and geographic region (North, Northeast, Southeast, South, and Midwest). Mortality rates were calculated using the Brazilian Mortality Information System and official national population estimates. An analytical ecological time series analysis was performed using the Prais–Winsten regression model to assess the DM-related mortality trends in two scenarios: before (2010–2019) and including the pandemic period (2010–2023). The annual percentage change (APC) and 95% confidence intervals (CIs) were calculated to synthesize the trends as decreasing, increasing, or stationary. DM-related mortality rates varied from 42.3 in 2010 to 35.9 per 100,000 deaths in 2023, with the highest values in the Northeastern region. An increase in mortality was observed from 2020 onwards. Regression analysis shows a decreasing trend in the pre-pandemic period (2010–2019) in women (−1.87%), 50–69 years (−1.24%), and ≥70 years (−1.21%). A decline was also observed in the Northeast (−1.06%), Southeast (−1.73%), and nationwide (−0.96%). However, after incorporating data from the pandemic period (2010–2023), the trend became stationary for individuals aged 50–69 years and ≥70 years, the Southeastern region, and Brazil. This change makes the expected mortality uncertain and highlights the need for effective coping strategies after the pandemic.